Enzymatization of Nila Fish (Oreochromis Niloticus) Protein Hydolysate by Combination of Bromelin and Pepsin Enzymes - Emma Zaidar Nasution; Laila Marhamah Nasution (Journal of Chemical Natural Resources, 2024)
Nile Tilapia (Oreochromis niloticus) is a freshwater fish with better nutritional content compared to other freshwater fish, making it suitable for use as a source for protein hydrolysate production. Protein hydrolysate is the result of the breakdown of protein into short-chain compounds through hydrolysis. This research aims to hydrolyze the minced Nile tilapia meat using a combination of bromelain and pepsin enzymes at a concentration of 5% and pH 7 conditions for 5-6 hours. The hydrolysis results using the combination of bromelain and pepsin enzymes (B100: P0) have a yield value of 12.68%, ash content of 2.94%, protein of 57.25%, water 2.65%, and fat 10.25% with a degree of hydrolysis of 61.46%. The hydrolysate has antibacterial properties against Staphylococcus aureus and Escherichia coli bacteria with inhibition zones of approximately 8.3 mm and 8.5 mm, respectively, at a concentration of 1 (mg/ÂµL), contains 15 types of amino acids with the highest composition being lysine 5.12% and the highest non-essential amino acid being aspartic acid 5.75%.